INCREASING EMPLOYMENT OPPORTUNITIES IN SMALL BUSINESS - Kholmirzaev Ikromjon , Odiljon oglu (THE INNOVATION ECONOMY, 2025)
This article examines the prospects for enhancing labor potential in small business entities in Uzbekistan. The study analyzes the impact of employee skills, working conditions, and motivation systems. A mixed-methods was employed approach, combining qualitative analysis (of legislation and enterprise documents) and quantitative analysis (of statistical data for 2020–2024). Findings indicate that skill development and motivation measures improved efficiency, but financial constraints, infrastructure issues, and educational gaps persist. Recommendations are tailored and provided to Uzbekistan’s context.